2019
DOI: 10.1177/1941738118824293
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors That Contribute to Adolescent Bony Stress Injury in Secondary School Athletes: A Comparative Analysis With a Healthy Athletic Control Group

Abstract: Background:Bony stress injuries (BSIs) are common among adolescents involved in high school sports. A better understanding of factors that contribute to adolescent BSI is needed to target preventative measures.Hypothesis:Individuals who suffer a BSI will demonstrate significant differences in training methods, sleep, diet, and history of injury compared with a healthy, noninjured control group.Study Design:Descriptive epidemiologic study.Methods:Data from the National High School Stress Fracture Registry (NHSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Longitudinal studies investigating high school athletes report that the preponderance of stress fractures (63%) occur in girls and that female athletes experience higher grades of stress fracture than males [ 16 , 50 , 75 ]. A higher incidence of female BSI than male is prevalent across a wide variety of sports at the high school and collegiate levels [ 15 , 16 ].…”
Section: Risk Factors For Bone Stress Injuries In Adolescent Athletesmentioning
confidence: 99%
See 3 more Smart Citations
“…Longitudinal studies investigating high school athletes report that the preponderance of stress fractures (63%) occur in girls and that female athletes experience higher grades of stress fracture than males [ 16 , 50 , 75 ]. A higher incidence of female BSI than male is prevalent across a wide variety of sports at the high school and collegiate levels [ 15 , 16 ].…”
Section: Risk Factors For Bone Stress Injuries In Adolescent Athletesmentioning
confidence: 99%
“…Disturbed sleep patterns in the adolescent athlete due to training commitments, social habits, academic requirements and use of technological devices affect physiological recovery and thus may predispose to injury [ 102 ]; however, self-reported sleep and stress levels appear to be better in elite athletes than age- and sex-matched non-athletes [ 103 ]. However, general psychological stress and poor sleep was associated with BSI in adolescent girls [ 75 ] and adolescents who have less than eight hours of sleep per night over an extended period are more likely to experience general injury [ 104 ]. A large-scale military study found that introducing a minimum sleep regimen (6 h) reduced incidence of stress fractures in new Israeli recruits (minimum age 18) from 31% to 11% [ 105 ].…”
Section: Risk Factors For Bone Stress Injuries In Adolescent Athletesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 95 endurance sport athletes who self-reported their sleep time over a 2-week period, those who slept <7 h/day were at a 51% increased risk of new injury, whereas athletes who slept >7 h/day reduced new injury risk by 37% (Johnston et al, 2020). Specific to BSI, in a population of 314 adolescent high school athletes who experienced 346 BSIs over a 2-year period, those with BSI reported sleeping less than those without a BSI (7.2 vs. 7.95 h/day) (Nussbaum et al, 2019). Figure 1, reprinted from Swanson et al (2018) with permission, demonstrates the complex, yet important, intersection between sleep and bone health.…”
Section: Recoverymentioning
confidence: 94%